Ona tili darslarini mahsuldor mashqlar orqali o‗quvchilar nutqini yangi so‗zlar bilan boyitish (SCIENCE and SOCIETY, 2024)
The possibility of increasing the share of productive exercises in the system of receptive, reproductive and productive exercises with the aim of increasing students’ speech, in particular, vocabulary, in the native language classes of primary grade was highlighted.